Exploring the elements : a complete guide to the periodic table - Thomas, Isabel, 1979- (Phaidon Press, Inc., 2020)
Presents information about the periodic table of elements including the properties, characteristics, roles, and forms and uses of each element. Includes color illustrations, a glossary, and additional resources.